Auf der Jagd nach der Sonne Das journalistische Feld und die Atomkraft in Japan. - Weiß, Tobias (Politische Soziologie, 2019)
The book is an analysis of the portrayal of nuclear power in Japanese journalism and the factors influencing it. Combining a field theoretical approach to journalism with frame analysis on different levels of the communica-tion process, the author argues that the nuclear industry in Japan used their financial power to build up a "pro-nuclear civil society" and that this frame-sponsoring is the reason for the relatively positive portrayal of nucle-ar power until 2011. After "Fukushima" the journalistic autonomy in this domain increased and journalism became a driving force of change in nuclear policy. At the same time the journalistic field became polarized because the more heteronomous parts of the field remain integrated into the "pronuclear civil society". The book offers a new perspective on Japanese media and journalism scholarship, emphasizing heterogeneity and change in contrast to previous scholarship, that has focused on press clubs as institutions of pervasive media control.